Constraints on superoxide mediated formation of manganese oxides - Learman, Deric R.; Voelker, Bettina M.; Madden, Andrew S.; Hansel, Colleen M. (Frontiers in Microbiology, 2013)
Manganese (Mn) oxides are among the most reactive sorbents and oxidants within the environment, where they play a central role in the cycling of nutrients, metals, and carbon. Recent discoveries have identified superoxide (O2-) (both of biogenic and abiogenic origin) as an effective oxidant of Mn(II) leading to the formation of Mn oxides. Here we examined the conditions under which abiotically produced superoxide led to oxidative precipitation of Mn and the solid-phases produced. Oxidized Mn, as both aqueous Mn(III) and Mn(III/IV) oxides, was only observed in the presence of active catalase, indicating that hydrogen peroxide, a product of the reaction of O2- with Mn(II), inhibits the oxidation process presumably through the reduction of Mn(III). Citrate and pyrophosphate increased the yield of oxidized Mn but decreased the amount of Mn oxide produced via formation of Mn(III)-ligand complexes. While complexing ligands played a role in stabilizing Mn(III), they did not eliminate the inhibition of net Mn(III) formation by H2O2. The Mn oxides precipitated were highly disordered colloidal hexagonal birnessite, similar to those produced by biotically generated superoxide. Yet, in contrast to the large particulate Mn oxides formed by biogenic superoxide, abiotic Mn oxides did not ripen to larger, more crystalline phases. This suggests that the deposition of crystalline Mn oxides within the environment requires a biological, or at least organic, influence. This work provides the first direct evidence that, under conditions relevant to natural waters, oxidation of Mn(II) by superoxide can occur and lead to formation of Mn oxides. For organisms that oxidize Mn(II) by producing superoxide, these findings may also point to other microbially mediated processes, in particular enzymatic hydrogen peroxide degradation and/or production of organic ligand metabolites, that allow for Mn oxide formation.